A waltz, not a tango in East Asia Regionalism: China and Japan searching for leadership. - Simões, Leticia Cordeiro; de Amorim, Wellington Dantas; de Carvalho, Patrícia Nasser (Cadernos de Estudos Sociais e Políticos, 2013)
Abstract: East Asia regionalism is one of the most puzzling integration processes in the world due to its particularities. Nevertheless, ASEAN has become a magnet to the process. China, Japan and South Korea have not missed the opportunity and became attached to ASEAN through APT. China and Japan are now in a fierce contest over leadership, using all the available tools. This paper aims to study this contest, with a look at the theoretical framework regarding leadership to East Asia. Then, Chinese and Japanese strategies towards the region will be analyzed, as well as the views of countries of the region regarding China’s and Japan’s influence and their quest for regional leadership. Paper information: Paper presented at International Studies Association Annual Convention (San Francisco- CA 2013) Resumo: O regionalismo do Leste Asiático é um dos mais intrigantes processos de integração do mundo devido as suas particularidades. No entanto, a ASEAN se tornou um imã para o processo. China, Japão e Coréia do Sul não perderam a oportunidade e se ligaram a ASEAN através da ASEAN+3. China e Japão estão agora em uma disputa acirrada pela liderança, utilizando todas as ferramentas disponíveis. Este artigo busca estudar esta disputa, utilizando-se de um arcabouço teórico de liderança. As estratégias chinesas e japonesas para a região serão analisadas, assim como os pontos de vista dos países da região a respeito da influência de China e Japão e sua busca pela liderança regional. Informação do artigo: Artigo apresentado na Convenção Anual da Internationa Studies Association (ISA)(San Francisco-CA 2013)